Clinical differences in sirolimus treatment with low target levels between children and adults with vascular malformations - A nationwide trial - Veroniek E. M. Harbers; Lilly G. J. M. Zwerink; Gerard A. Rongen; Willemijn M. Klein; Carine J. M. van derVleuten; Ingrid M. P. vanRijnsoever; Lynda Gerdsen‐Drury; Uta E. Flucke; Bas H. Verhoeven; Peter C. J. deLaat; Chantal M. A. M. van derHorst; Leo J. Schultze Kool; et al. (Wiley, 2023)
Abstract The clinical presentation of patients with slow‐flow vascular malformations is very heterogeneous. High clinical burden and subsequent reduced health‐related quality of life is something they have in common. There is an unmet medical need for these patients for whom regular treatments like surgery and embolization are either insufficient or technically impossible. Sirolimus has been reported to be effective and overall well‐tolerated in most patients. However, the main limitation of sirolimus is the reported high toxicity, especially when target levels of 10-15 ng/mL are being used. We report the results of a phase IIB single‐arm open‐label clinical trial consisting of 68 (67 in the challenge phase and 68 in the rechallenge phase) evaluable patients (children n = 33 and adults n = 35) demonstrating that treatment with low sirolimus target levels (4-10 ng/mL) is effective in 79.1% of the patients. When sirolimus treatment was stopped, the majority of patients experienced a recurrence of symptoms, supporting prolonged or even lifelong treatment requirement. Adults experienced a higher baseline pain score compared with children, having an estimated marginal mean of 6.2 versus 4.1, p < 0.05; however, they showed a similar decrease to children. Furthermore, the pediatric population experienced less often a sirolimus‐related grade I-IV adverse event (35.9% vs. 64.1%, p > 0.05) compared with adults. Additionally, response rates were higher in children compared with adults (93.8% vs. 65.7%, p < 0.05), and children responded faster (28 vs. 91 days, p < 0.05). These results suggest benefits of sirolimus in patients with slow‐flow vascular malformations and support its initiation as young as possible.